Correlation of Capacity Based Design and Force Based Design of Reinforced Concrete Structure (International Journal of Innovative Research in Engineering & Management, 2022)
The main cause of failure of multi-storey  multi-bay reinforced concrete frames during seismic  motion is the soft storey sway mechanism or column sway  mechanism. If the frame is designed on the basis of strong  column-weak beam concept the possibilities of collapse  due to sway mechanisms can be completely eliminated. In  multi storey frame this can be achieved by allowing the  plastic hinges to form, in predetermined sequences only at  the ends of all the beams while the columns remain  essentially in elastic stage and by avoiding shear mode of  failures in columns and beams. This procedure for design  is known as Capacity Based Design (CBD) which would  be safer than current design philosophy used for  earthquake resistant design of multi storey multi bay  reinforced concrete frames in India. The present Dissertation work is an effort to understand  Capacity Based Design Approach. In this Work a three  storey workshop building a linear static analysis is carried  out and then building is designed by force based method.  Then for Capacity Based Design columns are designed for  magnified moment by moment magnification factor. A  mechanism is applied to subsequent failure of storey  before vertical members by strengthening the columns  with respect of beams. Apart from improving axial  strength of columns, shear capacity of beams and columns  also improved in capacity based method. Reinforcement  obtained from this design compared to Force Based Design  and concluded that CBD method is little conservative but  it ensure to prevent column sway mechanism.
Keywords: Capacity Based Design; Reinforced concrete; Ductility; Beams and Columns